METHOD (MANHAJ) OF PROSELYTIZING OF THE PROPHET IN THE PHASE OF MAKKAH AND MEDINA - Agusman; Muhammad Hanif (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2022)
Thirteen years of proselytizing in Makkah and ten years in Medina were periods of the struggle of the Prophet Muhammad to lay the foundations of Islam on the face of the earth. The Prophet had gone through all forms of conditions and challenges of proselytizing, even having to deal with close relatives who opposed Islamic proselytizing. This condition further strengthened and strengthened the principle of the Prophet's proselytizing struggle in the early days of seeding the beauty of Islam in all corners of Arabia. Despite strong resistance from his people, the Prophet remained steadfast and was able to cultivate proselytizing wisely. The portrait of the Prophet's proselytizing is the perfection of the manhaj of proselytizing, so the pattern of the Prophet in proselytizing must be the main qibla for a da'i in regulating the pattern of his proselytizing in society, of course, by adjusting to the conditions of today's times. Manhaj dakwah Nabi became an important and mandatory reference for every da'i, to know how muslims should behave when facing proselytizing land in society.